CATATAN ELEKTRONIK GAWATDARURAT BENCANA (CEGAB) UNTUK OPTIMALISASI MANAJEMEN BENCANA - Kipa Jundapri; Ade Irma Khairani; Mulkan Azhari; Nadia Febrina; Anggy Wulandari (LPPM Institut Pendidikan Nusantara Global, 2025)
Electronic Disaster Emergency (CEGaB) is a platform that can be used to record data on patients/victims undergoing treatment in disaster conditions so that it can help in recording patient/victim data, as well as to get an overview in preparing for future disaster mitigation, so that preparations in facing disasters such as preparing human resources in this case the number and profession of health workers needed, the epidemiology of diseases that appear when a disaster occurs, as well as the need for consumables such as medicines needed if a disaster occurs in the future.